The Effect of Natural Thermal Cycles on Rock Outcrops: Knowledge and Prospect - Merrien-Soukatchoff, Véronique; Gasc-Barbier, Muriel (Rock mechanics and rock engineering, 2023)
In recent years, interest in the effect of positive temperatures on rock faces has increased, as evidenced by the extensive literature on the subject. The subsurface rock masses of rock slopes are submitted to uncontrollable natural temperature cycles which cause deformation, displacement, opening and closing of discontinuities and can lead to surface failure or more important rockfalls. In this paper we offer a review of the publications on this theme focusing on in situ observations and measurements. Measurements are described and analysed considering conditions of temperature and insolation, displacements, strains, focusing on two French sites (Les Rochers de Valabres and La Roque-Gageac). Mechanical analysis is then performed. The impact of temperature variation is studied from basic assumptions to much more complex ones. Thermoelasticity is first assessed, and analytical computation is suggested, fracture mechanism and fatigue are also considered. Finally, we outline some challenges to be addressed in the coming years. Highlights The article reviews the accumulated knowledge on the effect of positive temperature changes on slope stability. Excluding the effect of water freezing and thawing. The different types of measurements are reviewed considering surface and in-depth measurements of temperature, displacements, fracture opening, and strain. Simple thermo-elastic analysis, alongside solutions from fracture mechanics are proposed. A focus is proposed on 2 French sites to illustrate interpretations. The conclusion summarizes the points of consensus, the aspects that are still under discussion among authors or should be more debated and open to pending challenges for the next years.